INTERCULTURAL RELATIONS IN COMMUNICATION RESEARCH: A DECOLONIAL APPROACH - Panis Kaseker, Mônica (2024)
The article discusses the decolonial epistemological proposal and the methodological practices of the non-indigenous research involving indigenous communicators. The proposal is to analyze the potential of sentimental cartography as a methodological path for an decolonial investigation, looking for approximations with perspective of “corazonar” and “sentipensar”. One of the most latent issues is neutralizing the Eurocentric perspective and extractive methodologies. In this way, decolonial research becomes an encounter between subjects in an ecology of knowledge, experienced with bodies, whose affectations deconstruct and construct other knowledge.